Career preferences and socio-economic background - Paul Schüle (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2023)
Career decisions, that is educational and occupational choice, are not only made by comparing expected incomes, but also by considering non-monetary rewards like social impact, chances of promotion, or the compatibility of work and family. In this paper, I use rich panel data from Germany to show that preferences about such aspects of a career as stated at age 17 are strong predictors of future earnings in the labor market. At the same time, these preferences differ significantly by socio-economic background, and intergenerational income persistence is reduced by 8-22 percent when accounting for career preferences.
Keywords: D01; D63; J24; J62; I38; 330; Equality of opportunity; intergenerational mobility; occupational choice